How Do Mental Health Nurses Define Success? A Comparative Study of Bed-Based and Community-Based Services. (2nd September 2021) - Bushell, Hannah; Lee, Stuart; Keppich-Arnold, Sandra; Anderson, Shelley; Batu, Gamze; Hopkins, Liza
Abstract: Nursing is the single largest professional group within both hospital and community mental health care services, however the role of mental health nurses in under-defined. The nursing workforce is also coming under increasing pressure from internal and external requirements, and nurses themselves are on the frontline of providing patient care in what can be a risky and unpredictable workplace environment. This project explored via interview the ways in which mental health nurses experience and reflect on their personal and professional feelings of nursing success. Participants were 19 nurses who were employed in a range of bed-based and community mental health services in inner south eastern Melbourne. This study complies with the Consolidated Criteria for Reporting Qualitative Research (COREQ). The findings of the project align with existing evidence from the literature. Factors which helped mental health nurses feel successful included: therapeutic success; good teamwork; targeted education; and feedback. Barriers to success included: patients/clients do not engage or recover; poor communication amongst staff; lack of psychological safety in the workplace; and lack of respect from management. Nurses in community settings were more able than nurses in bed-based settings to: make effective use of clinical supervision; make use of targeted training and educational offerings; and practice therapeutically and holistically. Project results offer an opportunity to understand nurses' motivations and reward systems. Better understanding of these issues can improve the way mental health care services manage their workforce planning, maintain staff personal wellbeing, increase staff retention and ultimately improve patient/client care.